Cultivo de plantas medicinales, aromáticas y gastronómicas. Una alternativa de trabajo para la agricultura familiar campesina en el Cantón Vinces. - Carriel Laje, Josselyn Daniela (2023)
Ecuador is a megadiverse country that has not yet finished taking advantage of the benefits that nature has. This research project links the cultivation of medicinal, aromatic and gastronomic plants as an alternative and work for peasant family agriculture. Therefore, the objectives set out in this work were: Promote the planting of Medicinal, Aromatic and Gastronomic Plants as a work alternative for peasant family agriculture in the Vinces Canton, Los Ríos Province, Highlight the qualities and benefits that plants provide medicinal, aromatic and gastronomical products and propose alternatives for the implementation of a peasant family farming program in Cantón Vinces, Province of Los Ríos. To make this project viable, relevant information obtained from scientific experiments, specialized publications and reports in high-impact journals, scientific texts, academic repositories, and qualified web portals was investigated. This information was submitted to the techniques of analysis, synthesis, paraphrasing, and summary, in order to clarify its wording and make it understandable to any reader. The findings revealed as a result of this investigation show that there is a demand for medicinal, aromatic and gastronomic plants in the country and abroad, but the ignorance of the small producer, in this case, in the Vinces Canton, has not made the incursion possible. in this agricultural activity. In general, both Peasant Family Agriculture and the families that are part of the Popular and Solidarity Economy System have as their main and common objective "to ensure the life of the family."